1955
DOI: 10.1113/jphysiol.1955.sp005254
|View full text |Cite
|
Sign up to set email alerts
|

The delay and blockage of sensory impulses in the dorsal root ganglion*

Abstract: The aim of the present series of experiments is to try to clarify these controversial issues and to determine whether the dorsal root ganglion modified in any way the passage of sensory impulses. Besides suffering a delay under normal conditions, the sensory impulses are found to be blocked in their passage through the dorsal root ganglion during the early relatively refractory period of the afferent fibres. METHODIn most of the experiments the 9th or 10th dorsal root ganglion of the frog (Hyla aurea, Rana cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1955
1955
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…6 b, A) should indicate that the centripetal conduction from the bifurcation to the dorsal root was blocked partly. Conse quently, the safety factor of the conduction from the bifurcation to the dorsal root might be smaller than that from the peripheral nerve to the bifurcation, as was argued by Dun (1955), but it should be larger than that from the dorsal root to the bifurcation.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…6 b, A) should indicate that the centripetal conduction from the bifurcation to the dorsal root was blocked partly. Conse quently, the safety factor of the conduction from the bifurcation to the dorsal root might be smaller than that from the peripheral nerve to the bifurcation, as was argued by Dun (1955), but it should be larger than that from the dorsal root to the bifurcation.…”
mentioning
confidence: 94%
“…3 The presence of the M spike in the intracellular record shows that the impulse from the peripheral nerve arrives at the bifurcation, but it does not immediately indicate that the same impulse further conducts to the dorsal root. However, Svaetichin (1951) observed that the impulse, elicited by stimulating a single fiber in the peripheral nerve, conducted to the dorsal root even when the block was noticed in the extracellular potential of the ganglion cell.…”
mentioning
confidence: 98%
“…The latter measurement frequently gave conduction velocities well in excess of the known maximum value of A a/f, axons in the cat. The discrepancy was presumably a consequence of the delay that can occur in transmission of an action potential into the dorsal root ganglion cell body (Dunn, 1955). Figure 5A shows the distribution of central delays of y-efferent facilitation by SAl afferents.…”
Section: Sa1 Mechanoreceptorsmentioning
confidence: 99%
“…As noted, regions of low conduction safety have been associated with branches (Grossman et al 1973;Dun, 1955;Ito & Takahashi, 1960;Yau, 1976), expansions and constrictions (Goldstein & Rall, 1976;Spira, Varom & Parnas, 1976) and other axonal specializations such as nodal distribution and demyelination (Waxman, Pappas & Bennett, 1972) or profound variation in the local density of Na+ channels (Zeevi, 1972;Ritchie & Rogart, 1977). Such features may present no obstacle to conduction at low rates of discharge, yet they may become completely impassable as the activity rate rises (Krnjeci6 & Miledi, 1959), suggesting that the resulting growth in depression may be responsible for the conduction block.…”
Section: Physiological Role Of Threshold Shiftsmentioning
confidence: 99%
“…Recent direct work from several laboratories (Smith & Hatt, 1976;Parnas, 1972; Grossman, Spira & Parnas, 1973;Yau, 1976;Van Essen, 1973) supports earlier observations and suggestions that not all branches of an axon are invaded by each spike (Adrian, 1920(Adrian, , 1921Lucas, 1917;Barron & Matthews, 1935;Krnjevic & Miledi, 1959;Howland, Lettvin, McCulloch,.Pitts & Wall, 1955, Raymond & Lettvin, 1969Chung, Raymond & Lettvin, 1970), and that bifurcations constitute regions of low conduction safety (Dun, 1955;Ito & Takahashi, 1960;Lloyd & McIntyre, 1950;Wall, Lettvin, McCulloch & Pitts, 1956). Probability for invasion of a branch is neither constant nor independent of activity (Raymond, 1969;Grossman et al 1973).…”
Section: Introductionmentioning
confidence: 99%